Ratio Estimator in Adaptive Cluster Sampling without Replacement of Networks - Nipaporn Chutiman; Monchaya Chiangpradit (Journal of Probability and Statistics)
In this paper, we study the estimators of the population total in adaptive cluster sampling by using the information of the auxiliary variable. The numerical examples showed that the ratio estimator in adaptive cluster sampling without replacement of networks is more efficient than the ratio estimators in adaptive cluster sampling without replacement of units.